2003
DOI: 10.14430/arctic634
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluating the Co-management Success Story

Abstract: ABSTRACT. The integration of science and traditional knowledge (TEK), a cornerstone of contemporary cooperative management, entails translating First Nation people's life experiences into forms compatible with state wildlife management (e.g., numbers and lines on maps), with all the risks of distortion inherent in any translation process. Even after such a translation, however, knowledge-integration remains fraught with difficulties, many of which seem on the surface to be technical or methodological. Surprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 6 publications
3
106
1
2
Order By: Relevance
“…Understanding the dynamics of the comanagement process for the let the leaders pass regulation suggests the need to consider the costs and benefits of various actors at various scales, from the individual hunter to communities, to First Nations, and territorial and federal governments, as well as the historical context from which the regulation emerged. As noted by several previous studies, comanagement is typically no panacea (Caulfield 1997, Kofinas http://www.ecologyandsociety.org/vol19/iss2/art7/ 1998, Nadasdy 2003a, Caulfield et al 2004, Natcher et al 2005. Despite early theoretical hopes of a northern wildlife comanagement leading to more effective resource management (e.g., Osherenko 1988, Usher 1986, the political conflicts of comanagement have in some cases led to significant problems (e.g., Nadasdy 2003a).…”
Section: Managing Resources With Tekmentioning
confidence: 98%
“…Understanding the dynamics of the comanagement process for the let the leaders pass regulation suggests the need to consider the costs and benefits of various actors at various scales, from the individual hunter to communities, to First Nations, and territorial and federal governments, as well as the historical context from which the regulation emerged. As noted by several previous studies, comanagement is typically no panacea (Caulfield 1997, Kofinas http://www.ecologyandsociety.org/vol19/iss2/art7/ 1998, Nadasdy 2003a, Caulfield et al 2004, Natcher et al 2005. Despite early theoretical hopes of a northern wildlife comanagement leading to more effective resource management (e.g., Osherenko 1988, Usher 1986, the political conflicts of comanagement have in some cases led to significant problems (e.g., Nadasdy 2003a).…”
Section: Managing Resources With Tekmentioning
confidence: 98%
“…It has become increasingly appreciated by the scientific community that TEK/LEK has enhanced our understanding of the ecology of species, and is valuable for their future management (Service et al 2014;Pardo-de-Santayana and Macía 2015). However, it is important to note that there are often limitations and biases in the methods commonly used to gather, analyze and represent TEK/LEK that can not only jeopardize the reliability and validity of the data collected, but potentially result in negative impacts for wildlife populations (Nadasdy 2003;Gilchrist et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…• The PPP paradigm results provide another decade of data to Howlett's (1994) study of First Nations policy change, indicating a continued failure to meaningfully implement the new paradigm in drinking water service provision; • The evident competition between new and assimilationist paradigm principles supports Weaver's (1990) prediction of a coexistence of old and new paradigms; • The non-technical factors influencing drinking water program success, such as the lack of First Nations control and the underlying institutional paradigm, corroborate Nadasdy's (2003) findings in the natural resource co-management field; • The PPP paradigm provides a lens for analysing federal government responses to First Nations issues, such as the 2010 Bill S-11 for First Nations drinking water regulation (Senate of Canada, 2010); and • The PPP experience in Canada provides a comparison for Indigenous policy reform taking place in other colonially structured countries. Australia, for example, has: (i) similarly abandoned its assimilationist policy paradigm in favour of a self-determination policy paradigm, (ii) not yet meaningfully implemented the new paradigm, (iii) not yet successfully devolved program services, and (iv) not yet accommodated the diversity in the Indigenous population (Sherwood & Edwards, 2006;Turner, 1997).…”
Section: Ppp Findings Within the Existing Body Of Knowledgementioning
confidence: 84%
“…In one case, Innu Nation members experienced concerns regarding their community's capacity to administer the institutional burden of self-government (Tanner, 2001). In another case, Kluane First Nation members perceived that the Dall sheep co-management process provided only token decision-making authority (Nadasdy, 2003). A final case stems from a policy review of natural resource management devolution to First Nations in the Yukon Territory, which found that the process was in fact one of deconcentration, not devolution 5 (Natcher & Davis, 2007).…”
Section: Policies Programs and Processes: An Overview Policiesmentioning
confidence: 99%